An evaluation of the theory and use of the acridine orange stain in enumerating bacterial populations - Tomimatsu, Gail Susan (Virginia Polytechnic Institute and State University, 1976)
Live and killed pure cultures of a Gram positive rod and a Gram negative rod isolated from Lake Bonney in Southern Victorialand, Antarctica, as well as water samples from an oligotrophic lake, were stained with varying concentrations and pHs of aqueous solutions of the fluorochrome, acridine orange (AO). Results from this study gave strong supportive evidence for the non-vital staining properties of acridine orange contrary to previous reports in the literature. Green fluorescence of cells is not a reliable indicator of viability; and fluorescence color alone cannot distinguish between detritus and bacteria. Instead, the resultant color of fluorescence, i.e., green or red, appeared to relate to AO concentration and cell permeability. Nevertheless, the fluorochrome appears to be useful, as well as reliable, in staining cells and other particulates for estimating total numbers of bacteria from aquatic systems such as Mountain Lake; however other results indicate that the AO epifluorescence technique, as used in this investigation, may not be reliable in every instance. Master of Science